2000
DOI: 10.1080/14794800008520074
|View full text |Cite
|
Sign up to set email alerts
|

Visualisation and the Influence of Technology in ‘A’ Level Mathematics: A Classroom Investigation

Abstract: The study reported here is part of a wider study, which aims to investigate the potential of the graphical calculator for mediating the development of students' abilities to visualise the graphs of functions at GCE Advanced level. This paper focuses on how the graphical calculator influenced six particular students' work with functions. Initial results have illuminated ways in which the technology can have a positive impact on students' visualisation capabilities. It is proposed that visual thinking forms a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This is where the technology is powerful in facilitating the creation of many images rapidly in order to focus participants on the connections between them. Technology is also engaging and provides a change from the "normal" (forum Elliot (1998) [who] see visualisation as 'the relationship between images' to explain the boys' actions of using the software to sketch straight line graphs of equations inputted by them and improve their equations based on the feedback from the software (an indicator of his RiTPACK). He then explains how each time the feedback scaffolds the boys' learning in order to visualise there is a need to create many images to construct relationships that will facilitate visualisation and reasoning and concludes that the boys did benefit from the digital environment as in this thinking process another image is added to their visual understanding and they gain further clarity (End of Theme A task, week 4).…”
Section: The Case Of Markmentioning
confidence: 99%
“…This is where the technology is powerful in facilitating the creation of many images rapidly in order to focus participants on the connections between them. Technology is also engaging and provides a change from the "normal" (forum Elliot (1998) [who] see visualisation as 'the relationship between images' to explain the boys' actions of using the software to sketch straight line graphs of equations inputted by them and improve their equations based on the feedback from the software (an indicator of his RiTPACK). He then explains how each time the feedback scaffolds the boys' learning in order to visualise there is a need to create many images to construct relationships that will facilitate visualisation and reasoning and concludes that the boys did benefit from the digital environment as in this thinking process another image is added to their visual understanding and they gain further clarity (End of Theme A task, week 4).…”
Section: The Case Of Markmentioning
confidence: 99%
“…Appropriate teaching approaches are thus crucial in GeoGebra-supported lessons to help students better manipulate digital tools and understand mathematical concepts. Therefore, in line with the framework of Technological Pedagogical Content Knowledge (TPACK), this paper aims to develop Previous studies have identified multiple difficulties in regard to quadratic functions, such as the misinterpretation of symmetrical lines and extreme points [5], sketching a quadratic function by looking at the difference in values of coefficients and solving simultaneous equations graphically. In accordance with my designed activity, this paper focuses on students' common difficulty in building the relationship between the algebraic equation of a quadratic function and a geometric graph [6].…”
Section: Introductionmentioning
confidence: 99%
“…They argue that computer based curriculum materials can give an "improved cognitive base" leading to a more powerful and flexible understanding of the mathematical concept. In a similar way, Carulla and Gomez (1997) note that technology can enable students to develop a greater "insight" into the relationship between graphs and functions and Elliott and Hudson (2000) suggest that a factor in allowing such insight to occur is that numerous functions and graphs can be demonstrated by a teacher in an effective manner that would not be possible with a whiteboard. Our study considers the way in which the computer enables the teacher, not to demonstrate numerous functions and graphs, but to allow the students to engage in exploring many different graphs and the outcome of such an approach.…”
mentioning
confidence: 99%